One stop shop II: taxonomic update with molecular phylogeny for important phytopathogenic genera: 26–50 (2019) - Ruvishika S. Jayawardena (2019)
© 2019, School of Science. This paper is the second in a series focused on providing a stable platform for the taxonomy of phytopathogenic fungi. It focuses on 25 phytopathogenic genera: Alternaria, Bipolaris, Boeremia, Botryosphaeria, Calonectria, Coniella, Corticiaceae, Curvularia, Elsinoe, Entyloma, Erythricium, Fomitiporia, Fulviformes, Laetisaria, Limonomyces, Neofabraea, Neofusicoccum, Phaeoacremonium, Phellinotus, Phyllosticta, Plenodomus, Pseudopyricularia, Tilletia, Venturia and Waitea, using recent molecular data, up to date names and the latest taxonomic insights. For each genus a taxonomic background, diversity aspects, species identification and classification based on molecular phylogeny and recommended genetic markers are provided. In this study, varieties of the genus Boeremia have been elevated to species level. Botryosphaeria, Bipolaris, Curvularia, Neofusicoccum and Phyllosticta that were included in the One Stop Shop 1 paper are provided with updated entries, as many new species have been introduced to these genera.